2018
DOI: 10.1039/c7ay02808c
|View full text |Cite
|
Sign up to set email alerts
|

Ion mobility derived collision cross section as an additional measure to support the rapid analysis of abused drugs and toxic compounds using electrospray ion mobility time-of-flight mass spectrometry

Abstract: Despite recent advances in analytical techniques, high-throughput and rapid screening of abused drugs and toxic compounds is imperative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 26 publications
3
21
0
Order By: Relevance
“…In consideration of the DTIM- study, most compounds are in accordance and show only little deviation. For example, CCS values of fenuron, flufenacet, and others differ less than 1% from the CCS values provided by Regueiro et al 12 The CCS values published by Bijlsma et al, 42 Lian et al, 43 Zheng et al, 44 and Møllerup et al 45 show also similar values (deviation ≤ 1%) compared to CCS values reported in this study (e.g., metalaxyl, metolachlor, and metoprolol; for details, see Table S-3). However, some deviate more than 1%, which is a common tolerance range for database searches (e.g., bisoprolol).…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…In consideration of the DTIM- study, most compounds are in accordance and show only little deviation. For example, CCS values of fenuron, flufenacet, and others differ less than 1% from the CCS values provided by Regueiro et al 12 The CCS values published by Bijlsma et al, 42 Lian et al, 43 Zheng et al, 44 and Møllerup et al 45 show also similar values (deviation ≤ 1%) compared to CCS values reported in this study (e.g., metalaxyl, metolachlor, and metoprolol; for details, see Table S-3). However, some deviate more than 1%, which is a common tolerance range for database searches (e.g., bisoprolol).…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…While not an exhaustive list, a few of the larger libraries to note are: Li and colleagues' peptide database which includes >2300 CCS values,13 Pagel and colleagues' glycomics database of >900 CCS values,14 and Xu and colleagues' small molecule database containing >1400 CCS values 15. Additionally, many excellent smaller CCS libraries have been generated for lipids,1618 primary metabolites,1820 secondary metabolites and other natural products,18,21,22 as well as illicit substances23 among others.…”
Section: Introductionmentioning
confidence: 99%
“…have originally proposed an acceptable deviation of 2% between CCSs measured in samples and reference CCS values in databases [ 34 , 42 ]. Although this criterion has been applied in current LC-IMS-MS workflows intended for food or biological analysis [ [43] , [44] , [45] , [46] ], a recent inter-laboratory study has shown that the tolerance for CCS measurements can be potentially reduced to ±0.5% when using DTIMS [ 47 ]. Thus, more studies are still needed, not only to ensure that complex sample matrices do not influence the drift time and, as a consequence, affect CCS measurements [ 48 , 49 ], but also to validate or reduce the threshold of ±2% currently accepted for CCS measurements.…”
Section: Introductionmentioning
confidence: 99%